PENGARUH PENERAPAN MODEL PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI SMP NEGERI MODEL TERPADU MADANI PALU - Samara, Daud (Katalogis, 2016)
This research aims at identifying the differences in the learning achievement Â between students who were taught by using the ASSURE learning model to those whom were taught by using conventional learning model; interaction between learning model and learning motivation; the difference between learning achievement of high and low motivated students. The sample of this research is Chairil Anwar VIII grade consisted of 28 students as the control class. The design of this research is quasi experiment 2 x 2. The treatment variable is learning model and the attribute variable is learning motivation, while the dependent variable is the learning achievement of Social Sciences subject. The hypothesis was tested through ANAVA two ways with different cells to significant level of 5%. The result of the differences between ASSURE model learning achievement and conventional proven by the score of statistic test where Fcounted = 7.084 and Ftable = 5.79 or Ho is rejected. It means that there is difference between learning achievement of ASSURE class to the conventional class. The score of statistic test where Fcounted = 25.27 and Ftable = 5.79 or Ho is rejected. It means that there is difference between group of high motivated students and group of low motivated students. The score of statistic test between motivation and learning model where Fcounted = 0.010 and Ftable = 5.79 or Ho is accepted. It means that there is no interaction and affect to the learning achievement between learning model to learning motivation.